Analysis of Work Motivation Regarding Fixed Income Reception (Siltap) Among Village Officials in Sisobahili Village, Gido District, Nias Regency - Laoli, Yosea; Mendrofa, Syah Abadi (Amkop Management Accounting Review (AMAR), 2025)
This study examines the factors influencing village officials' work ethic regarding the receipt of Fixed Income (Siltap) in Sisobahili Village, Gido District, Nias Regency. Using qualitative methods, the research conducted in-depth interviews with three key informants: the Village Head, the Head of General Affairs and Planning, and the Head of Welfare. Data was collected through observation, structured interviews, and documentation, and analyzed using Miles and Huberman's interactive model. Findings reveal supporting factors include timely Siltap disbursement, income certainty, and administrative transparency. Inhibiting factors encompass disbursement delays, insufficient non-financial rewards, and disproportionate workload distribution. Results show a significant positive correlation between timely Siltap disbursement and work motivation levels. The village government optimizes motivation through consistent disbursement timing, improved financial transparency, competency development training, and integrated performance evaluation systems. Siltap functions as both a financial compensation and a strategic motivation tool, fostering accountability and professionalism. Recommendations include maintaining consistent disbursement, developing non-material appreciation systems, and optimizing workload distribution.